The twilight saga. Breaking dawn. Part 1 [videorecording (Blu-Ray)] - Condon, Bill, 1955-; Stewart, Kristen, 1990-; Pattinson, Robert, 1986-; Lautner, Taylor, 1992-; Burke, Billy; Facinelli, Peter, 1973-; Rosenberg, Melissa; Godfrey, Wyck; Rosenfelt, Karen; Burwell, Carter; Meyer, Stephenie, 1973- (Summit Entertainment, 2012)
In the highly anticipated fourth installment of the Twilight Saga, a marriage, a honeymoon, and the birth of a child bring unforeseen and shocking developments for Bella and Edward and those they love, including new complications with young werewolf Jacob Black.